Molecular Identification and Intra-species Variations among Leishmania infantum Isolated from Human and Canine Visceral Leishmaniasis in Iran - Abdolhossein DALIMI (Iranian Journal of Parasitology, 2018)
Background: In Iran, both forms of cutaneous (CL) and visceral leishmaniasis (VL) have been re-ported; so the accurate species identification of the parasite(s) and the analysis of genetic diversity are necessary.